2011
DOI: 10.1530/eje-10-1129
|View full text |Cite
|
Sign up to set email alerts
|

Impaired quality of life and sexual function in overweight and obese men: the European Male Ageing Study

Abstract: Background: Few published data link overweight and obesity with measures of quality of life (QoL) including sexual health in men. Objective: To assess the association of overweight/obesity with impairment of physical and psychological QoL and sexual functions in men. Design and setting: Cross-sectional, multicentre survey of 3369 community-dwelling men aged 40-79 (meanGS.D., 60G11) years randomly selected from eight European centres. Outcomes: Adiposity was assessed by body mass index (BMI) and waist circumfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 39 publications
4
54
2
5
Order By: Relevance
“…International Index of Erectile Function (IIEF). The IIEF is a widely-used, 15-item scale that assesses 5 domains of male sexual functioning: erectile function (range: 0-30); orgasmic function (0-10); sexual desire (2-10); intercourse satisfaction (0-15); and overall satisfaction (2)(3)(4)(5)(6)(7)(8)(9)(10). Lower scores indicate less satisfaction and greater dysfunction [30,31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…International Index of Erectile Function (IIEF). The IIEF is a widely-used, 15-item scale that assesses 5 domains of male sexual functioning: erectile function (range: 0-30); orgasmic function (0-10); sexual desire (2-10); intercourse satisfaction (0-15); and overall satisfaction (2)(3)(4)(5)(6)(7)(8)(9)(10). Lower scores indicate less satisfaction and greater dysfunction [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies have found a relationship between extreme obesity and impairments in quality of life, as well as greater depressive symptoms and increased body image dissatisfaction [3][4][5][6][7]. Individuals with obesity often report untoward changes in sexual functioning and decreased sexual satisfaction [6,[8][9][10][11][12][13]. In a recent study of individuals with extreme obesity who presented for bariatric surgery, 51% of women and 36% of men reported a sexual dysfunction [13].…”
mentioning
confidence: 99%
“…Physical activity and a low-calorie diet allow weight loss, self-image improvement and better quality of life, as well as better sexual function and satisfaction [47][48][49][50]. There is, however, limited data as to whether reduction in body weight by itself would improve sexual function.…”
Section: Sexual Fantasiesmentioning
confidence: 99%
“…However, the cross-sectional association between low T and symptoms was attenuated after adjusting for body mass index (BMI) and comorbidities (5), underlining the multicausal origin of putative symptoms of hypogonadism in ageing men. Moreover, obesity, independent of T, is associated with sexual (9) and psychological symptoms (10) as well as impaired physical activity (11). Confirming the appearance of these symptoms with the development of biochemical hypogonadism and/or their resolution following recovery to eugonadism (EUG) would support their relevance as specific clinical markers of androgen deficiency, important in the diagnostic workup of men with low T.…”
mentioning
confidence: 99%